Digital Currencies and Energy Consumption - Agur, Itai (FinTech Notes; FinTech Notes ;, 2022)
Whether in crypto assets or in CBDCs, design choices can make an important difference to the energy consumption of digital currencies. This paper establishes the main components and technological options that determine the energy profile of digital currencies. It draws on academic and industry estimates to compare digital currencies to each other and to existing payment systems and derives implications for the design of environmentally friendly CBDCs. For distributed ledger technologies, the key factors affecting energy consumption are the ability to control participation and the consensus algorithm. While crypto assets like Bitcoin are wasteful in terms of resources, other designs could be more energy efficient than existing payment systems.